Impact of Teacher Motivation on Student Engagement and Classroom Behavior in Secondary Schools - Khumairah, Nurul; Ramlah, Ramlah; Muin, Nurfadillah (Educia Journal, 2023)
This paper seeks to establish selected elements of teacher motivation to their respective effects on classroom behaviours, of particular interest are Intrinsic motivation, Extrinsic motivation, job satisfaction and professional development. This study adopted a quantitative method; 150 teachers from different schools in Makassar City were administrated questionnaires, and regression analysis was used to test the level of teacher motivation and classroom dynamics. The findings show that type of motivation plays a huge role in the classroom, with self-interest having the greatest impact on student attentiveness. It also shows that job satisfaction is reducing rate of poor classroom behavior and enhancing teacher-student communication, while professional development enhances teacher student relationship. The results of extrinsic motivation were also noticeable but lower than intrinsic motivation. The research findings offer an important contribution to future research in the field, as they offered an overall picture of teacher motives and their implications for different aspects of classroom dynamics. The study has focused on the need for education policies that encourage the growth of intrinsic motivation through organisational work culture and staff due process. This shows that by addressing motivation at this level schools are likely to create teacher incentive of the positive environment that is most likely to enhance the learning process of the students. The study has practical implications to upgrading the educational practices; it is recommended that increasing the level of teacher motivation leads to development of better classroom climate, therefore promoting a better education.